Clinical Perspectives on the Notion of Presence - Malet, Pascal; Bioy, Antoine; Santarpia, Alfonso (Frontiers in Psychology, 2022)
This article explores the theme of presence of the psychotherapist, a concept that has been of par-ticular interest in humanistic and existential approaches. Presence was first associated with the hu-manistic attitudes of the practitioner and the way he or she embodies these attitudes in the here and now of the encounter. Since the publication in 2002 of Geller and Greenberg's model of therapeutic presence, several quantitative studies have explored the relationship between the therapist's perception of presence and other dimensions of the therapeutic process. However, qualitative explorations still seem necessary to account for the complexity of the therapist's presence and its role in the therapeutic process. Centered on the therapist’s perspective, we use an idiographic methodology and refer to lived clini-cal experience to highlight the dimension of sensory contact that, through the body, actualize a con-nection to a virtual space of the therapeutic relationship. We so describe how a therapist can achieve an embodied processing to clinical material from what we describe as “traces of presence” of the other. From this point of view, the patient's presence incorporates itself into the therapist's experience and the therapist can perceive aspects of this presence in a tangible, concrete, and useful way. The thera-pist's presence thus takes on a meaning that is not reduced to what the patient will perceive and in-terpret of his or her attitude. It becomes the main material from which the therapist orients his or her clinical interventions.